PSYCHOLOGICAL DESCRIPTION OF SELF-REALIZATION AMONG DEPRIVED PEOPLE - Tarjumanyan, S.V. (Modern Psychology, 2021)
The article is dedicated to the psychological description of self-realization among deprived people. It was observed the problem of self-realization and deprivation, what is 349 deprivation, who are deprived people, and what specifications are there in the process of self-realization. The article discusses the differences between the consequences among different people, making it obvious- that even though different people having the same situation of deprivation will have different psychological images depending on their self-schemas- there are some phenomena that are very typical for deprived people. It is assumed, that deprivation causes some negative changes in person’s psyche; especially the deprivation that person had during childhood will influence on the process of self-realization in adult life, by preventing its forming.
Keywords: deprivation, self-consciousness, self-actualization, self-esteem, emotional image.